2000
DOI: 10.1080/08927010009378442
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory behaviour of barnacle larvae in field conditions

Abstract: The aim of this work was to develop techniques for the real time filming of Semibalanus balanoides cyprid larvae in the field in order to describe the exploratory behaviour of S. balanoides cyprids under natural field conditions. The underwater camera system consisted of a high resolution, remotely controlled colour camera attached to a cradle which could be deployed from a pier. A light utilising a battery of far-red light-emitting diodes (λ min = 615 nm) was used for filming at night. Transparent acrylic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…5). Walters (1992), Lemire & Bourget (1996) and Walters et al (1999) Hills et al (2000) and Matsumura et al (2000) observed a much lower proportion of settlement for Semibalanus balanoides cyprids in short-term fieldbased behavioural studies (<1% settled during 30 min recording intervals). The high propensity for settlement on smooth substrata explains the dominant role of B. improvisus as a fouling organism on boat hulls in the Baltic, Kattegatt and Skagerrak Seas.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5). Walters (1992), Lemire & Bourget (1996) and Walters et al (1999) Hills et al (2000) and Matsumura et al (2000) observed a much lower proportion of settlement for Semibalanus balanoides cyprids in short-term fieldbased behavioural studies (<1% settled during 30 min recording intervals). The high propensity for settlement on smooth substrata explains the dominant role of B. improvisus as a fouling organism on boat hulls in the Baltic, Kattegatt and Skagerrak Seas.…”
Section: Discussionmentioning
confidence: 90%
“…Hills et al 1998, Walters et al 1999, Berntsson et al 2000a), but may not correspond to natural conditions in the field where larvae are subjected to several stimuli simultaneously (e.g. Hills et al 2000). As advocated by Zimmer & Butman (2000), studies of larval responses should be performed in the presence of major stimuli experienced in the field to avoid serious artefacts.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…However, the endogenous neurotransmitters, neurohormones, neuromodulators and intracellular signal pathways involved in the regulation of barnacle larval settlement is as yet not fully revealed (Clare and Matsamura, 2000). Several studies describe intriguing behavioural mechanisms (Crisp, '61;Berntsson et al, 2000;Hills et al, The results are presented as an increase in the mean percentage settlement by the addition of methoxy-idazoxan as compared with the dishes where larvae were subjected to the inhibitor alone and no methoxy-idazoxan was added.The concentration refers to both the concentration of the inhibitor and methoxy-idazoxan. In those cases where the settlement in the dishes with the inhibitor was zero, this value was set to 1.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Larvae significantly altered their surface exploratory behaviour between day and night, in terms of gross and net distance travelled, speed and heading angle.…”
Section: S Balanoides [27]mentioning
confidence: 99%